Procedimento para identificação do regime de escoamento das bolhas dispersas em uma mistura gás-líquido escoando em tubos verticais - Assis, Guilherme Marodin (2015)
Gas-liquid flows are encountered in many industrial applications such as in the oil industry, where a gas-oil mixture is transported through pipes from the well to the separation and processing facilities. The dispersed bubbles flow is one of the several gas-liquid flow patterns frequently found in this industrial application. Depending on the dispersed bubbles flow regime (viscous, distorted and turbulent), the flow characteristics change significantly, influencing the gas velocity and, therefore, changing the gas fraction along the pipe cross section. The goal of this study is to propose a solution procedure for flow regime identification and consequently, obtaining the main characteristics of the dispersed flow. The solution procedure was implemented in a computer code written in Fortran 95 programming language. For the results analysis, it was developed a computer code using Gnuplot application commands with the goal to generate a map of flow patterns which allows viewing and verifying the occurrence of dispersed bubbles regimes. The analysis results showed that the solution procedure captures the dispersed flow characteristics with a good precision, despite of the differences encountered due to the variation of the fluids physical properties and the pipe diameter in the analysed cases.